2014
DOI: 10.1155/2014/852489
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Survival and Retention among HIV-Infected Children and Adolescents in a Community Home-Based Care and a Facility-Based Family-Centred Approach in Kampala, Uganda: A Cohort Study

Abstract: We describe factors determining retention and survival among HIV-infected children and adolescents engaged in two health care delivery models in Kampala, Uganda: one is a community home-based care (CHBC) and the other is a facility-based family-centred approach (FBFCA). This retrospective cohort study reviewed records from children aged from 0 to 18 years engaged in the two models from 2003 to 2010 focussing on retention/loss to follow-up, mortality, use of antiretroviral therapy (ART), and clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 35 publications
7
26
0
Order By: Relevance
“…Similarly, a matched retrospective cohort study in 10 provinces of Mozambique demonstrated lower lost-to-follow-up rates among patients in Community Adherence and Support Groups than among those in individual care (11 versus 26 %) and lower overall attrition (12 versus 28 %), but similar mortality (1 % in both cohorts) [26]. Other studies have shown similar improvement in retention associated with community-based support but without clear mortality benefit [27, 28]. Only one recent study saw an improvement in mortality associated with community-based support, namely a descriptive case study of a community home-based care organization in Swaziland that provided individual and household support for ART adherence.…”
Section: Principles Of Community-based Therapymentioning
confidence: 99%
“…Similarly, a matched retrospective cohort study in 10 provinces of Mozambique demonstrated lower lost-to-follow-up rates among patients in Community Adherence and Support Groups than among those in individual care (11 versus 26 %) and lower overall attrition (12 versus 28 %), but similar mortality (1 % in both cohorts) [26]. Other studies have shown similar improvement in retention associated with community-based support but without clear mortality benefit [27, 28]. Only one recent study saw an improvement in mortality associated with community-based support, namely a descriptive case study of a community home-based care organization in Swaziland that provided individual and household support for ART adherence.…”
Section: Principles Of Community-based Therapymentioning
confidence: 99%
“…Adults were more likely to be initiated into HAART than children. 9 This obviously contributed to high rates of deaths and lost-to-follow up among ARV naïve children. In this study, disclosure of HIV status to the child ensured adherence to care and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment-eligible children living with HIV in sub-Saharan Africa are only about half as likely to receive antiretroviral therapy as HIV-positive adults. 9 Non-disclosure of HIV status to peri-natally infected children and adolescents is still a major concern in the sub-region. These have implications for adherence and treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown better patient retention among those who are on ART compared to those in pre-ART care. 5,15 If we adopt the new WHO policy of universal ART, 16 the need for pre-ART care would be limited. In the study setting, this would mean that an additional one third of children will become eligible for ART, which has resource implications.…”
Section: Public Health Actionmentioning
confidence: 99%